1995
DOI: 10.2172/104474
|View full text |Cite
|
Sign up to set email alerts
|

Geologic and tectonic characteristics of rockbursts

Abstract: DISCLAIMERThis document was prepared as an account of work sponsored b) an agenc) of the United States Government.\either the United States Government nor the Universit) of California nor an? of their emplojees. makes an) warrant?, express or implied, or assumes an) legal liabilitj or responsibilitj for the accurac?, completeness, or usefulness of an) information, apparatus, product, or process disclosed, or represents that its use wuuld not infringe privatel) owned rights. Reference herein to an) specific com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Calculations for estimation using formula (1) showed that by 01.01.2014, with an average decrease in reservoir pressure by 4.2 MPa since the beginning of field development, the water volume introduced into the reservoir, increased to 105 million m 3 . The gas volume extracted from pore-fractured space under reservoir conditions at a pressure of 16 MPa and a temperature of 32 ° C is estimated to be about 4.9 billion m 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations for estimation using formula (1) showed that by 01.01.2014, with an average decrease in reservoir pressure by 4.2 MPa since the beginning of field development, the water volume introduced into the reservoir, increased to 105 million m 3 . The gas volume extracted from pore-fractured space under reservoir conditions at a pressure of 16 MPa and a temperature of 32 ° C is estimated to be about 4.9 billion m 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Intensive oil and gas production in such large regions as Groningen gas field in Netherlands, War-Wink Field in USA, Romashkinskoye field and Orenburg oil and gas condensate field in Russia has disrupted natural environment [1][2][3], has significantly rebuilt hydro-gas-dynamic and geodynamic processes in the Earth's crust in the depth of more than ten kilometers on an area of several tens thousands of square kilometers. The conditions for emergence of a number of environmental problems have been created, which significantly affect nature development and life quality of population in the region.…”
Section: Introductionmentioning
confidence: 99%
“…As early as the 1950s and the 1960s, scientists in the United States and the Soviet Union noticed the triggering effect of underground nuclear explosions (Qian & Wnag, 2010). They noticed that a few days after an underground nuclear explosion, earthquakes sometimes occurred at distances of hundreds or even thousands of meters away, releasing significant amounts of energy (Adushkin & Turuntaev, 2015). When the nuclear explosion wave passed through a fault at the Semipalatinsk test site, the stress release of the faults resulted in abnormally large amplitudes of transverse and surface waves (Helle & Rugg, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of fluids can accelerate the redistribution of stress state. When rock mass is in a critical state, strong dynamic pulses can easily induce stress triggering of earthquakes (Adushkin & Spivak, 2007; Adushkin & Turuntaev, 2015).…”
Section: Introductionmentioning
confidence: 99%